Apakah Audit Judgment Dipengaruhi oleh Ukuran Perusahaan, Tekanan Ketaatan, dan Pengetahuan Auditor? - Winda Apriliastuty; Supri Wahyudi Utomo; Nur Wahyuning Sulistyowati (STATERA: Jurnal Akuntansi dan Keuangan, 2019)
This study aims to examine the effect of company size, compliance pressure, and auditor knowledge on audit judgment. This type of research is quantitative research. The sampling technique was purposive sampling with a sample of 18 companies 56 financial statements. The data analysis technique used in this study is a statistical regression using the IBM SPSS Statistics version 22 program. The results show that: obedience pressure and auditr knowledge influence audit judgment because obedience pressure is influenced by the client and the senior auditor and the level of knowledge influence judgment given the auditor. The size of the company does not affect audit judgment because a small amount of assets does not affect the evaluation results of the auditor's judgment.